Des transports publics pour tous (suite) ? Les trajets dans Bruxelles pour les personnes en situation de handicap - Frédéric Dobruszkes; Martin Grandjean; Arthur Nihoul (Brussels Studies, 2025)
This paper investigates the gap in PT access to the city faced by disabled people when using public transport in Brussels. The research is carried out at the route level from all STIB-MIVB stops to 20 selected destinations across the city. The calculations compare unconstrained accessibility with accessibility restricted by six different travel constraints. The results are very heterogeneous, depending on the travel constraint considered, the departure point and the destination. This study finds a large gap in PT access to the city: under travel constraints, most trips take more time, require more transfers and involve more walking. The non-inclusive nature of the underground network has a major impact on the results. We conclude that there is a lot of room to make public transport in Brussels truly inclusive.